THE PROFIT PREDICTION PUZZLE: HOW GROSS, OPERATING, AND NET PROFIT INFLUENCE FUTURE CASH FLOWS WITH A DEPRECIATION AND AMORTIZATION TWIST - Vista Yulianti; Sindik Widati; Dian Sulistyorini Wulandari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the effect of gross profit, operating profit, and net profit on predicting future cash flows, with depreciation and amortization (DA) as moderating variables. The data used in this research is secondary data from financial reports of manufacturing companies listed on the Indonesian Stock Exchange (IDX) from 2019 to 2023. The research applies panel data regression analysis, with Ordinary Least Squares (OLS), Fixed Effects, and Random Effects models to evaluate the impact of profitability measures on future cash flows. The results show that gross profit and operating profit have significant negative effects on future cash flows, while net profit has a significant positive effect. Furthermore, the introduction of DA as a moderating variable reveals that it significantly influences the relationship between gross profit and future cash flows, but does not significantly affect the relationship between net profit and cash flows. These findings suggest that non-cash expenses like depreciation and amortization should be considered when forecasting future financial performance.